2009
DOI: 10.1111/j.1440-6055.2009.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

The tolerance of the lucerne flea, Sminthurus viridis (Collembola: Sminthuridae), to currently registered pesticides in Australia

Abstract: Sminthurus viridis (lucerne flea) is a major crop and pasture pest throughout southern regions of Australia that experience a Mediterranean type climate. It is particularly problematic at the establishment phase, and chemicals are currently the main option available to farmers for their control. Few studies have assessed the currently registered pesticides for the control of S. viridis, and rates of application are generally similar to the frequently co-occurring red-legged earth mite, Halotydeus destructor, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Bioassays were used to determine whether H. destructor populations differed in their response to chemicals. The method employed was a glass vial technique modified for earth mites by Hoffmann et al 11 This is a proven technique that has been used numerous times to examine the chemical responses of mites, including H. destructor 14–17. For each concentration tested, about 20 mL of solution was poured into a 40 mL glass vial and swirled to ensure a complete coating, with excess liquid removed.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Bioassays were used to determine whether H. destructor populations differed in their response to chemicals. The method employed was a glass vial technique modified for earth mites by Hoffmann et al 11 This is a proven technique that has been used numerous times to examine the chemical responses of mites, including H. destructor 14–17. For each concentration tested, about 20 mL of solution was poured into a 40 mL glass vial and swirled to ensure a complete coating, with excess liquid removed.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…As the results of this study highlight, monitoring can identify when populations are reaching damaging levels and when vulnerable life stages are present. Various spraying regimes have been suggested by previous authors, although multiple pesticide applications are still often required (Roberts et al 2009). Bishop et al (2001b) assessed several early season spraying regimes and found a single spray once S. viridis reached damaging levels to be an effective and economical strategy.…”
Section: Discussionmentioning
confidence: 99%
“…(blue oat mite), species that are major grain pests and frequently targeted with insecticides because they attack crops at the vulnerable seedling stage . Recent studies have shown difficulties already exist when attempting to control these pests due to inherent tolerance to certain chemicals . Sminthurus viridis , for example, is sensitive to organophosphorus chemicals, but tolerant to pyrethroid chemicals .…”
Section: Resistance Status In Australian Grains and Industry Trendsmentioning
confidence: 99%
“…20 Recent studies have shown difficulties already exist when attempting to control these pests due to inherent tolerance to certain chemicals. [21][22][23] Sminthurus viridis, for example, is sensitive to organophosphorus chemicals, but tolerant to pyrethroid chemicals. 24 There are few registered chemical options available to control S. viridis and Australian farmers rely almost exclusively on organophosphates.…”
Section: Resistance Among Arthropod Grain Pestsmentioning
confidence: 99%